2013
DOI: 10.1001/jamapediatrics.2013.32
|View full text |Cite
|
Sign up to set email alerts
|

Association Between District and State Policies and US Public Elementary School Competitive Food and Beverage Environments

Abstract: Both district and state policies and/or laws have the potential to reduce in-school availability of high-sugar, high-fat foods and beverages. Given the need to reduce empty calories in children's diets, governmental policies at all levels may be an effective tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 34 publications
(36 reference statements)
2
39
0
Order By: Relevance
“…Beverage policies in schools have been associated with reduced student access and consumption of sugary drinks during school time. [28][29][30] However, less conclusive is whether school beverage policies influence students' overall daily consumption. 29,31 Studies are needed of the influence of child-care beverage policies on children's intakes.…”
Section: Implications For Practicementioning
confidence: 99%
“…Beverage policies in schools have been associated with reduced student access and consumption of sugary drinks during school time. [28][29][30] However, less conclusive is whether school beverage policies influence students' overall daily consumption. 29,31 Studies are needed of the influence of child-care beverage policies on children's intakes.…”
Section: Implications For Practicementioning
confidence: 99%
“…35 Results have been mixed for policy and school availability associations with student consumption. 3,4,611 Some studies have shown that school beverage availability is associated with overall student SSB consumption. 10,12 Other research examining only regular soda has indicated that state policy and school availability are associated with consumption among African American students, but not the general student population.…”
Section: Introductionmentioning
confidence: 99%
“…There also was poor alignment between some of the state- and district-level questions for the 2 models examining practices to promote healthy items. Future studies could examine these associations with state- and district-level data that more closely align as well as examine associations between state-level food and beverage marketing policies and school-level practices, because state policies have been important levers for other school nutrition changes (9,10). Future research could also try to identify other training and technical assistance topics that may help districts address food marketing, including identifying food and beverage marketing in the school setting and leveraging school wellness councils to address food marketing (1).…”
Section: Discussionmentioning
confidence: 99%